Chain mechanism in the photocleavage of phenacyl and pyridacyl esters in the presence of hydrogen donors - Literák, Jaromír; Dostálová, Anna; Klán, Petr (The Journal of organic chemistry, 2006)
[reaction: see text] Excited phenacyl and 3-pyridacyl esters of benzoic acid react with an excess of aliphatic alcohols in a chain reaction process involving hydrogen transfer from the ketyl radical intermediates, leading to benzoic acid in addition to acetophenone and 3-acetylpyridine, respectively, as the byproducts. While the maximum quantum yields reached 4 in both cases, the 2- or 4-pyridacyl ester photoreduction proceeded with the efficiency below 100% under the same conditions. The investigation indicates that a radical coupling between ketyl radicals, both formed from the excited ester by hydrogen abstraction from an alcohol, is accompanied by the elimination of benzoic acid from the ester ketyl radical itself. A partitioning between two reactions was found to be remarkably sensitive to the chromophore nature, such as a position of the nitrogen atom in the pyridacyl moiety. The magnitude of a radical chain process is dependent on the efficiency of consecutive steps that produce free radicals capable of a subsequent ester reduction. The driving force of a possible electron transfer from the ketyl radicals to the ester has been excluded on the basis of cyclic voltametry measurements. The observed quantum yields of photoreduction were found to be diminished by formation of relatively long-lived light absorbing transients, coproducts obtained apparently by secondary photochemical reactions. Additionally, it is shown that basic additives such as pyridine can further increase the efficiency of the photoreduction by a factor of 4. A radical nature of the reduction mechanism was supported by finding a large kinetic chain length of an analogous reaction initiated by free radicals generated thermally yet again when phenacyl or 3-pyridacyl benzoate was used. Both phenacyl and pyridacyl chromophores are pronounced to be valuable as the photoremovable protecting groups when high quantum and chemical yields of carboxylic acid elimination are important, but higher concentrations of the hydrogen atom donors are not destructive for a reaction system or are experimentally impractical.
Keywords: Photolysis; fenoly; Phenols; indikátory a reagencie; fotochemie; fotolýza; pyridiny; oxidace-redukce; Hydrogen; vodík; Photochemistry; benzoáty; spektrofotometrie ultrafialová; Oxidation-Reduction; Benzoates; Pyridines; Spectrophotometry, Ultraviolet; Indicators and Reagents